Thriving at work, career calling, and moral distress among nurses - Li, Fuda (Nursing ethics, 2024)
BackgroundEmergency nurses who thrive at work experience positive emotions that help reduce burnout and thus enhance career calling. However, few studies have focused on the relationships among thriving at work, career calling, and moral distress among emergency nurses.ObjectivesTo investigate the relationships among thriving at work, career calling, and moral distress and to explore the mediating role of career calling in the relationship between thriving at work and moral distress among emergency nurses.DesignA quantitative, cross-sectional study.MethodsA cross-sectional study was conducted by reference to 390 emergency nurses in China using an online survey that include the Thriving at Work Scale, the Career Calling Scale, and the Moral Distress Scale-Revised. The data were analyzed using SmartPLS software.Ethical considerationThe study was approved by the Ethics Committee of Hunan Normal University (No. 2023-388).FindingsAmong emergency nurses, thriving at work is positively associated with career calling, while career calling is negatively associated with moral distress. Career calling negatively and completely mediates the relationship between thriving at work and moral distress (β = −0.087, p < 0.01).DiscussionTheoretically, the findings enhance our understanding of the relationships among thriving at work, career calling, and moral distress among emergency nurses.ConclusionBy emphasizing the benefits of thriving at work, nursing managers can improve nurses’ level of thriving at work by providing a favorable environment, a flexible scheduling system, and appropriate authorization as well as by ensuring organizational fairness and providing training opportunities in a hierarchical manner.